On the Pre-council Municipality of Schleswig - Radkte, Christian (Hikuin, 1998)
Historiographical research has never questioned that the social structure of 12th-century Schleswig´was dominated by the Guild of long-distance merchants. The Guild was of equal importance to the ruling elements of the King and the Duke in its municipal constitution. Erich Hoffmann and Hans-Friedrich Schütt have devoted many articles to this subject and it has not been questioned by Scandinavian scholars; I have previously subscribed to this theory. The basic premise of this picture seemed to be clear and well -ordered. The long-distance merchants who dominated the economic life of the town of Schleswig are thought to have united in a Guild by at least the time of Duke Knud Laward (1115-1131). This Guild could represent their interests and also offer protection and security for long-distance traders who were far away from their families. The Guild is thought to have participated in peace-keeping and jurisdiction through the system of ‘Eideshilfe’ (help granted by oath) and also to have influenced the rules of market life and the currency. According to Hoffmann, the Guild’s local Scandinavian and imported continental organizational functions were united into a new totality in Schleswig. The head of this Schleswig Guild was apparently the Duke himself.